2018
DOI: 10.14740/jocmr3202w
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Thyroid Lesions in Western Region of Saudi Arabia: A Retrospective Analysis and Literature Review

Abstract: BackgroundUltrasonography (US) is being recognized as a traditional way of the diagnosis of various thyroid disorders, and this will help in detecting the thyroid tumors in early stage. Thyroid nodules are common and usually benign; steps to diagnose malignancy should include a careful clinical evaluation, laboratory tests, a thyroid US exam and a fine-needle aspiration (FNA) biopsy.MethodsA total of 173 registered cases were used for analysis in this study. Diagnosis was made following US-guided FNA cytology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
24
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 39 publications
9
24
5
Order By: Relevance
“…A high prevalence of thyroid cancer was seen in our patients with thyroid nodules (13.4% of the females and 18.4% of the males), and there was no significant difference in the rate of cancer among those with single nodules and multiple nodules (P value = 0.07); this is similar to what was reported by Frates et al [16], and the highest rate of cancer was among those with nodules 1-2 cm in size; this is similar to a study that showed the highest malignancy rate among nodules < 2 cm in size [17]. The overall prevalence of cancer among patients with thyroid nodules was 13.8%, which is higher than that in neighboring countries, which is reported to be approximately 9-10% [8][9][10]. TSH level was significantly associated with thyroid cancer (P -value 0.01), which is consistent with studies that showed an increased risk of thyroid cancer with an increase in TSH level [12,18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A high prevalence of thyroid cancer was seen in our patients with thyroid nodules (13.4% of the females and 18.4% of the males), and there was no significant difference in the rate of cancer among those with single nodules and multiple nodules (P value = 0.07); this is similar to what was reported by Frates et al [16], and the highest rate of cancer was among those with nodules 1-2 cm in size; this is similar to a study that showed the highest malignancy rate among nodules < 2 cm in size [17]. The overall prevalence of cancer among patients with thyroid nodules was 13.8%, which is higher than that in neighboring countries, which is reported to be approximately 9-10% [8][9][10]. TSH level was significantly associated with thyroid cancer (P -value 0.01), which is consistent with studies that showed an increased risk of thyroid cancer with an increase in TSH level [12,18].…”
Section: Discussionsupporting
confidence: 90%
“…Other countries with high incidence rates include the USA (13.2), Canada (12.7), Turkey (10.9) and Italy (10.8) [6,7]. Other studies from the Middle East showed thyroid cancer in 10.5% of patients with thyroid nodules in Jordan [8] and rates of 5% in Saudi Arabia in one study [9] and 10.4% in another [10]. In the United Arab Emirates, the prevalence was 9% among those of Emirati origin [11] and 5% among those with thyroid nodules in Pakistan [12].…”
Section: Introductionmentioning
confidence: 94%
“…In the current study, thyroid lesions affected females more than males (85% vs. 15%), this result was consistent with multiple previous studies by Saeed MI et al, Richman DM et al, Ram N et al, and Germano A et al, who reported lesion rates in females of 87.3%, 82.8%, 80%, and 79%, respectively 13-16. The results were also consistent with a previous study by Dalia et al, who reported that TNs in females are four times more common than in males.…”
Section: Discussionsupporting
confidence: 93%
“…This study identified benign lesions in 106 (84.1%) female cases and 20 (15.9%) male cases, but all malignant cases were in females. These results were consistent with those of Saeed et al, who reported that benign lesions were 87.4% in females and 12.6% in males, while malignant lesions were 87.5% in females and 12.5% in males 13…”
Section: Discussionsupporting
confidence: 93%
“…The incidence is more common among females compared to males. The prevalence of thyroid cancer 10.1% [5] and the common malignant type being papillary thyroid carcinoma [27] .…”
Section: Introductionmentioning
confidence: 99%